Pengembangan dan Karakterisasi Filter Berbasis Kitosan dari Limbah Kulit Udang dan Aplikasinya sebagai Media Filtrasi Mikroplastik - Rizki Sandhi Titisari; Daffa Hifrizi; Laily Isrofiani; Sapto P. Putro; Samuel Andre Yulianto; Farrel Rahman Parwoto; Andya Setya P. Putro (Jurnal Penelitian Pendidikan IPA, 2026)
Microplastics persist in aquatic systems and are difficult to remove using conventional filtration methods, prompting the development of low-cost, bio-based alternatives. This study presents a proof-of-concept chitosan filter derived from shrimp-shell waste, evaluated as a membrane sheet and as a coating on cellulose filter papers. FTIR confirmed chitosan formation, showing characteristic –OH/–NH stretching (~3450 cm⁻¹), amide I (~1650 cm⁻¹), amide II (~1570 cm⁻¹), and polysaccharide fingerprint peaks (1200–1000 cm⁻¹). Filtration experiments used a fixed 50 mL mixed-microplastic suspension processed under vacuum through five media: chitosan membrane, coffee filter paper, Whatman No. 42, and their chitosan-coated variants. Filtration time was recorded to derive the apparent filtration rate, and retained residues were assessed by visual inspection, stereomicroscopy, and morphometric size measurements in Fiji (particle size range reported as projected digital measurements). Coffee-based media exhibited the highest throughput (>50 mL/min), the chitosan membrane showed intermediate throughput (10 mL/min), and Whatman-based media were the slowest (7.14 mL/min). Chitosan-containing media displayed localized deposition and broader retained size ranges (up to 3.5 µm) compared with uncoated cellulose. Overall, the results support a waste-to-resource chitosan filtration approach that adds surface-mediated retention alongside passive sieving, with promising potential for application in laboratory-scale and pilot-scale wastewater treatment systems